P-type semiconducting gas sensing behavior of nanoporous rf sputtered CaCu3Ti4O12 thin films - Joanni, E. [UNESP]; Savu, R. [UNESP]; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2008)
The fabrication of nanoporous sputtered CaCu3Ti4O12 thin films with high gas sensitivity is reported in this work. The porous microstructure and the nanocrystalline nature of the material promoted the diffusion of the atmosphere into the film, shortening the response time of the samples. Behaving as p-type semiconductor, the material presents enhanced sensitivity even at low working temperatures. Impedance spectroscopy measurements were performed in order to investigate the mechanisms responsible for the performance of the devices. (C) 2008 American Institute of Physics.